Sharing Identity through Indigenous Tourism: Osoyoos Indian Band’s Nk’Mip Desert Cultural Centre - Bresner, Katie (Anthropologica, 2014)
Expressing a visual, indigenous identity in tourism can be a balancing act between maintaining a level of recogni tion and familiarity that mirrors the expectations of the public imagination and conveying a representation that is locally meaningful and emblematic to hosts. This article addresses this issue through the example of the Nk’Mip Desert Cultural Centre, owned and operated by the Osoyoos Indian Band (OIB) of British Columbia. Semiotic and visual analyses were used to explain the messages about OIB identity that the Centre communicates and to provide a framework to discuss three main issues in tourism discourse: control, hybridity and authenticity.